An investigation on trade openness, fiscal policy and economic growth in Malaysia: using an ARDL bounds testing approach - Abdullah, Hussin; Mohd Mustafa, Muszafarshah; Habibullah, Muzafar Shah (Universiti Utara Malaysia Press, 2009)
This study examines the impacts of trade openness and fiscal policy on economic growth in Malaysia between 1970 and 2003 using the autoregressive distributed lag (ARDL) approach and bounds test as proposed by Pesaran et al. (2001). Based on a structure consistent with the endogenous growth theory, the ARDL results show that, overall, trade openness and fiscal policy have strong positive impacts on economic growth in Malaysia over this period. This paper also develops a system instrumental variable method to estimate the structural speed of adjustment coefficient in an error correction model.